The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1016/j.bbmt.2008.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Mobilization and Remobilization Strategies on Achieving Sufficient Stem Cell Yields for Autologous Transplantation

Abstract: The purpose of this article was to examine historic institutional autologous stem cell mobilization practices and evaluate factors influencing mobilization failure and kinetics. In this retrospective study we analyzed clinical records of 1834 patients who underwent stem cell mobilization for autologous transplantation from November 1995 to October 2006 at the Washington University in St. Louis. Successful mobilization was defined as collection of > or =2 x 10(6) CD34(+) cells/kg. From 1834 consecutive patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

24
354
1
12

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 324 publications
(398 citation statements)
references
References 46 publications
24
354
1
12
Order By: Relevance
“…Overall, the patients were characterized by features that are known to affect standard stem cell mobilization negatively, including advanced age, a diagnosis of NHL, previous radiotherapy, extensive treatment with chemotherapy, treatment with lenalidomide or purine analogues, previous autoSCT, or failure of at least one previous attempt at mobilization [7][8][9][10][11][12][13][14][15]. We observed that, despite these unfavorable characteristics, mobilization with plerixafor and G-CSF enabled the required number of stem cells to be collected in 67.5% of patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overall, the patients were characterized by features that are known to affect standard stem cell mobilization negatively, including advanced age, a diagnosis of NHL, previous radiotherapy, extensive treatment with chemotherapy, treatment with lenalidomide or purine analogues, previous autoSCT, or failure of at least one previous attempt at mobilization [7][8][9][10][11][12][13][14][15]. We observed that, despite these unfavorable characteristics, mobilization with plerixafor and G-CSF enabled the required number of stem cells to be collected in 67.5% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…A number of factors are known to affect the outcome of stem cell mobilization negatively in the context of traditional mobilization regimens that are based on the administration of G-CSF with or without chemotherapy. These factors include advanced age, a diagnosis of non-Hodgkin's lymphoma (NHL), previous radiotherapy, extensive treatment with chemotherapy, treatment with lenalidomide or purine analogues, and the failure of at least one previous attempt at mobilization [7][8][9][10]. In this study, we decided to investigate whether the above-mentioned factors might allow the prediction of a suboptimal outcome for stem cell mobilization with plerixafor and G-CSF.…”
Section: Introductionmentioning
confidence: 99%
“…However, the combination of G-CSF and GM-CSF is used as a salvage mobilization regimen when mobilization with G-CSF alone has been unsuccessful. 23,47,99 Boeve et al 23 remobilized stem cells in 86 patients in whom a previous mobilization attempt with G-CSF alone had failed. Nineteen patients received a daily regimen of G-CSF 10 mg/kg plus GM-CSF 5 mg/kg from 4 days before apheresis until the end of PBSC collection, and the remaining 67 patients received high-dose G-CSF (16 mg/kg twice daily).…”
Section: Mobilization Agent Mechanismmentioning
confidence: 99%
“…43,44 The utility of all current mobilization regimens is limited by their high failure rates, which are estimated to be from 5 to 30%, regardless of the approach. 26,[45][46][47] The question of whether failure rates after chemomobilization are lower than failure rates after cytokine-only mobilization has not been adequately studied. There remains a significant controversy over the question of which method of PBSC mobilization is the safest and most predictable.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, plerixafor, formerly known as AMD-3100, was shown to be useful in association with G-CSF for a proportion of poorly mobilizing patients. [9][10][11][12] Recombinant human SCF (rhSCF) or ancestim has also been used in this patient subset.…”
Section: Introductionmentioning
confidence: 99%